Autism specific pedagogic intervention (ASP) - Ahmad, Abdulbaghi (Henry Stewart Talks, 2018)
Autism Spectrum Disorder (ASD): criteria, definitions and clinical picture, ASD cases in Iraqi Kurdistan, The Metin Health House, Autism-Specific Pedagogic Intervention (ASP): a novel individually adjusted intervention, Results from first case studies